2019
DOI: 10.1002/hyp.13603
|View full text |Cite
|
Sign up to set email alerts
|

The compensating effect of glaciers: Characterizing the relation between interannual streamflow variability and glacier cover

Abstract: Meltwater from glaciers is not only a stable source of water but also affects downstream streamflow dynamics. One of these dynamics is the interannual variability of streamflow. Glaciers can moderate streamflow variability because the runoff in the glacierized part, driven by temperature, correlates negatively with the runoff in the non-glacierized part of a catchment, driven by precipitation, thereby counterbalancing each other. This is also called the glacier compensation effect (GCE), and the effect is assu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 56 publications
2
22
0
Order By: Relevance
“…Often, these conclusions are drawn from modeling exercises that allow separating the glacier melt contribution from other streamflow contributions such as snowmelt, rainfall runoff, and groundwater. However, modeling these glacierized hydrological systems is a challenge because of the many intertwined hydrological processes (Finger et al, 2011;Konz and Seibert, 2010;van Tiel et al, 2020b). Hence, models may only give a rough estimation of the different streamflow contributions and may not adequately simulate the hydrological processes during extreme warm and dry periods.…”
Section: Introductionmentioning
confidence: 99%
“…Often, these conclusions are drawn from modeling exercises that allow separating the glacier melt contribution from other streamflow contributions such as snowmelt, rainfall runoff, and groundwater. However, modeling these glacierized hydrological systems is a challenge because of the many intertwined hydrological processes (Finger et al, 2011;Konz and Seibert, 2010;van Tiel et al, 2020b). Hence, models may only give a rough estimation of the different streamflow contributions and may not adequately simulate the hydrological processes during extreme warm and dry periods.…”
Section: Introductionmentioning
confidence: 99%
“…These two catchment parts can thus counterbalance each other and reduce the inter‐annual streamflow variability (Chen & Ohmura, 1990; Fountain & Tangborn, 1985). However, van Tiel, Kohn, Van Loon, and Stahl (2020) showed that this compensation effect depends not only on the relative glacier cover in the catchment. Besides the marked seasonality, diurnal variations in summer streamflow strongly reflect temperature and radiation variation throughout the day (e.g., Lane & Nienow, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of glaciers alters the watershed's response in both the timing and magnitude of the peak discharge because glaciers act as natural water reservoirs at the watershed scale and because summer precipitation has to be routed through the glacier before reaching the stream. Hence, the hydrograph of a glacierized watershed is expected to exhibit less variability than that of a nonglacierized one (Fleming & Clark, 2005;Fountain & Tangborn, 1985;Jansson et al, 2003;Van Tiel et al, 2019;Walder & Fountain, 1998). Similarly, lakes accumulate snowmelt, rainfall, and glacier melt during the ablation season and release water when sufficiently filled.…”
Section: Hydrological Regimesmentioning
confidence: 99%